Experimental Study of Rice Husk Fluidization Without a Sand Bed Material on a Bubbling Fluidized Bed Gasifier - Abeth Novria Sonjaya; Kania Safitri; Adi Surjosatyo (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
This study aimed to determine the effect of rice husk fluidization and variation in the equivalence ratio of bubbling fluidized bed gasifiers without sand bed materials. It also aimed to improve the fluidization quality by reducing the diameter of rice husks. Therefore, the bulk density increases, whereas voidage decreases, both of which are the main parameters for improving the quality of fluidization in solid particles. Experiments were carried out at a velocity of 0.82 m/s, by varying the equivalent ratios ranging from 0.20 to 0.35, and analyzing the syngas composition, cold gas and carbon conversion efficiencies, lower heating value, and temperature distribution. An equivalence ratio of 0.30 was obtained for a bubbling fluidized gasifier with syngas compositions of 7.415%, 15.674%, 3.071%, 17.839%, and 56.031% for H2, CO, CH4, CO2, and N2, respectively. Under these conditions, we obtained cold gas and carbon conversion efficiencies and a lower heating value of 31.340%, 37.120%, and 3.881 MJ/Nm3, respectively.